Development of A Liquid-Phase Microextraction Method for Simultaneous Determination of Parabens in Lipstick Samples at Trace Levels by High-Performance Liquid Chromatography - Gosterisli, Tugce U.; Kublay, Irem Z.; Keyf, Seyfullah; Bakirdere, Sezgin (OXFORD UNIV PRESS INC, 2024)
The endocrine-disrupting potential of parabens, as well as their relation to cancer, has sparked significant discussions over their impact. Consequently, analyses of cosmetic products are an essential necessity, particularly in terms of human health and safety. In this study, a highly accurate and sensitive liquid-phase-based microextraction method was developed to determine the five parabens at trace levels by high-performance liquid chromatography. All prominent parameters of the method such as extraction solvent type and amount (1,2-dichloroethane/250 mu L), and dispersive solvent type and amount (isopropyl alcohol/2.0 mL) were optimized to enhance the extraction efficiency of the analytes. The mobile phase consisting of 50 mM ammonium formate aqueous solution (pH 4.0) and acetonitrile (60:40, v/v) was used to elute the analytes at a flow rate of 1.2 mL min(-1) in the isocratic mode. Analytical performance of the optimum method for methyl, ethyl, propyl, butyl and benzyl parabens were determined and the analytes recorded detection limit values of 0.78, 0.75, 0.34, 0.33 and 0.75 mu g kg(-1), respectively. Four different lipstick samples were analyzed under optimum conditions of the developed method, and the amount of parabens quantified in the samples using matrix matched calibration standards was in the range of 0.11-1.03%.
Keywords: PRESERVATIVES; EXPOSURE; DERIVATIZATION; EXTRACTION; COSMETICS; ESTERS; MS/MS; WATER; Biochemistry & Molecular Biology; Chemistry